A Novel Cell-based In vitro Assay for Antiviral Activity of Interferons α, β, and γ by qPCR of MxA Gene Expression - Saber, Mohamed A.; Okasha, Hend; Khorshed, Fatma; Samir, Safia (Recent Patents on Biotechnology, 2021)
Background: Human MxA gene is related to the class of interferon (IFN)-stimulated genes (ISGs) that plays a role in antiviral resistance. Objective: Implementation of standard curves obtained from designing a procedure for data processing in relative qPCR between MxA expression and interferon’s antiviral activity (IU/ml). These standard curves can be used to detect the antiviral activity of any new compound rapidly and safely. Methods: To detect the optimum incubation time for maximum MxA gene expression in human peripheral blood mononuclear cells (PBMC), the isolated human PBMCs (1x106 cells) were incubated with a concentration of 1000 IU/ml of each IFN at different time intervals; 2 h, 4 h, 6 h, and 24 h post-treatment. A standard curve was performed for each IFN (α, β, and γ) at different concentrations (250, 500, 750, 1000, 1500, and 2000 IU/ml). Results: As observed at 4 h incubation time of 1000 IU/ml concentration, IFN-γ provided a higher expression of MxA compared to IFN-α and IFN-β. Correlation analyses between IFN-α and IFN-β, IFN-β and IFN-γ were non-significant. However, there was a significant correlation between IFN-α and IFN-γ (p<0.01). Receiver operator characteristic (ROC) analysis revealed that cut-off values of IFN- γ, IFN-β, and IFN-α were 58.14 > 7.31 and > 3.33, respectively. Conclusions: The relative expression of MxA is a biomarker for IFN-α, β, and γ, especially IFN-α. It has compiled and validated a standard curve-based protocol for PCR data processing. It shows that the standard curve is an easy alternative tool to assess antiviral activity. We revised all patents relating to the antiviral assays of the used interferons.
Keywords: antiviral